Protection of Minors Who Are Victims of Child Trafficking (Human Trafficking) - Harahap, Abdul Aziz; Hasanah, Uswatun (Universitas Islam Negeri Sumatera Utara, 2024)
Human trafficking is a transnational crime that is often committed across national borders. The victims also vary and it is not uncommon for children to be targeted as victims of this crime. The method in this research is normative research aimed at knowing the forms of legal rules, legal principles, and legal doctrines to answer the issues at hand to be imposed on the perpetrators of this human trafficking crime. And to find out also what kind of protection and assistance will be obtained by children who are victims of the crime of human trafficking in accordance with the laws and regulations in force in Indonesia.